Sífilis na gestação: série histórica da doença no município de Belém-PA no período de 2008 a 2017 - SOUSA, Eder Pinheiro de (2023)
Introduction: Syphilis is a disease caused by Treponema pallidum and transmitted sexually, hematogenously or vertically at any time during pregnancy. The Ministry of Health indicates its routine screening to all pregnant women who perform prenatal care. However, the incidence of the disease remains high, posing a public health challenge. Objective: To describe the epidemiological profile of syphilis in the city of Belém-PA, from 2008 to 2017. Method: Epidemiological, retrospective, descriptive study, from 2008 to 2017 in the city of Belém-PA. Results: The number of cases of syphilis during pregnancy increased considerably from 2013 to 2016, with the most affected women being in the age group of 20 to 29 years and 31% of the cases occurred in adolescents, most of whom had schooling less than or equal to incomplete primary education, race / color brown, and the most frequent clinical classification was primary syphilis. Conclusion: The situation of syphilis in pregnant women in the city of Belém does not seem to express the epidemiological reality of this disease, either because of lack of information or because of doubtful information. It is recommended that further studies on this topic be conducted in the region in order to deepen the knowledge aimed at the health needs of patients with syphilis during pregnancy.